Proximity labeling: methods and protocols - Sünbül, Murat; Jäschke, Andres (Methods in molecular biology, 2019)
The EMARS Reaction for Proximity Labeling -- Proteomic Proximity Labelling to Reveal Interactions Between Biomolecules -- Establishing Cell Culture-based Experimental Setups for Proximity Labeling Using Ascorbate Peroxidase (APEX) -- APEX Peroxidase Catalyzed Proximity Labeling and Multiplexed Quantitative Proteomics -- Identification of Lipid Droplet Proteomes by Proximity Labeling Proteomics Using APEX2 -- Antibody-driven Proximity Labeling in Fixed Tissues -- BioID: A Method to Generate a History of Protein Associations -- Direct Identification of Biotinylated Proteins from Proximity Labeling (Spot-BioID) -- Identifying Synaptic Proteins by in vivo BioID from Mouse Brain -- A Proximity Ligation-based Method to Detect RNA-DNA Association -- Enzymatic Transfer of Photo-cross-linkers for RNA-Protein Photo-cross-linking at the mRNA 5'-cap -- Proximity-induced Bioorthogonal Chemistry Using Inverse Electron Demand Diels-Alder Reaction -- Overcoming the Limitations of Sortase with Proximity-based Sortase-mediated Ligation (PBSL) -- Proximity-driven Site-specific and Covalent Labeling of Proteins with a TexasRed Fluorophore Reacting (ReacTR) Peptide Tag -- Affinity Conjugation for Rapid and Covalent Labeling of Proteins in Live Cells -- Ligand-directed N-Sulfonyl Pyridone Chemistry for Selective Native Protein Labeling and Imaging in Live Cell